Leaching of heavy metal(loid)s from historical Pb–Zn mining tailing in abandoned tailing deposit: Up-flow column and batch tests. (1st January 2023) - Yao, Yuan; Tong, Lizhi; Zhao, Ruolin; Wang, Qianhui; Qiu, Jinli; Wang, Fenghe; Li, Jining; Yan, Yifan; He, Yue; Li, Shuqin
Abstract: This study aims to investigate the water-leaching characteristics of heavy metal(loid)s (HMs) from historical Pb–Zn mine tailing of an abandoned tailing deposit in eastern China. Up-flow column and batch leaching tests were conducted at different liquid-to-solid (L/S) ratios to estimate the releases of HMs and investigate the controlling mechanisms. Calcite and silicate were the dominant minerals in the tailing and the HMs contents followed the order of Zn (2371 mg/kg) > Pb (2061 mg/kg) > Cu (109 mg/kg) > Cr (47.8 mg/kg) > As (15.9 mg/kg) > Cd (5.1 mg/kg). Moreover, considerable fractions of Pb, Zn, and Cd existed in the acid-soluble forms (41–47%). Column and batch leaching tests consistently showed that limited quantities (<0.002%) of HMs could be leached from this historical tailing. In particular, variations in column conditions (e.g., length, flow rate, and initial saturation) significantly affected the release fluxes from the columns but had a relatively limited effect on the leaching mechanisms. The estimated results of HM release suggested that the leaching process was predominantly solubility-controlled and the dissolution of Ca-bearing minerals (e.g., calcite) primarily controlled the release of HMs. The studied tailing had a limited impact on the quality of the surrounding aquatic environments because the water-leaching concentrations of HMs were generally lower than the Chinese standards for drinking water. Only for Pb, the leaching results in column tests were significantly lower than those in batch tests; whereas the results in column tests for other HMs were comparable to those in batch tests to a certain extent. Based on the column test results, the amounts of HMs potentially released from the abandoned tailing deposit (height, 10 m; footprint area, 30, 000 m 2 ; tailing dry density, 1.9 × 10 3 kg/m 3 ) followed a decreasing order of Zn (4.2 × 10 5 kg) > Cu (2.3 × 10 4 kg) > Pb (1.4 × 10 4 kg) > Cr (2.3 × 10 4 kg) > Cd (1.6 × 10 3 kg) > As (1.2 × 10 3 kg) over the 75-year assessment period (corresponding to an L/S ratio of 10 L/kg with an annual precipitation of 1500 mm). Graphical abstract: Image 1 Highlights: Leaching of HMs from historical LZT was compared in batch and column tests. Most Pb, Zn and Cd existed in the acid-soluble form. Quite limited HMs could be leached by water from the LZT. Dissolution of Ca-bearing minerals predominantly controlled the HMs releases. Year-dependent potential mass releases of HMs from the tailing deposit were estimated.